Possibility of Enhancing Students’ Academic Performance in Electrolysis using Collaborative-Predict-Observe-Explain-Write (CPOEW) and 3E’s Learning Models (British Journal of Multidisciplinary and Advanced Studies, 2024)
This research investigated the possibility of enhancing senior secondary school students’ academic performance in electrolysis using Collaborative-Predict-Observe-Explain-Write (CPOEW) and Exploration, Explanation and Evaluation (3E’s) learning models. The study adopted a quasi-experimental research design. Electrolysis Performance Test (EPT) was the instrument used for data collection. Kuder-Richardson (KR-21) formula was used to test the internal consistency of EPT which yielded a reliability value of 0.91. The population was 7,152 SS2 students offering chemistry in Makurdi, Benue State, Nigeria. A sample of 143 students drawn from 3 schools in Makurdi Local Government Area of Benue State, Nigeria was selected using multi-stage sampling techniques. Two research questions and two null hypotheses guided the study. The research questions were answered using Mean and Standard Deviation scores while the null hypotheses were tested at 0.05 level of significance using results from Analysis of Covariance (ANCOVA). The study revealed that there was significant difference in the mean academic performance of students taught Electrolysis using CPOEW, 3E’s model and discussion method [F2, 140=1943.116, P